2020
DOI: 10.1016/j.jcf.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 seroprevalence in a Belgian cohort of patients with cystic fibrosis

Abstract: Background In Belgium, COVID-19 epidemy began on February 4, 2020 with a peak on April 10, 2020. Patients with cystic fibrosis (CF) followed in the Cliniques universitaires Saint-Luc were rapidly isolated before the government lockdown. Methods After the peak of the epidemy, we measured anti-SARS-CoV-2 IgM and IgG antibodies in 149 patients and collected clinical data. Results Only 3 asymptomatic patients presented IgG against the virus. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…We cannot rule out that the testing strategy during the first phase of the pandemic, with only symptomatic patients being tested by PCR and limited use of serological tests, could have led to an underestimation of the real infection rate. However, seroprevalence data from Belgium seem to confirm the low infection rate in the CF population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot rule out that the testing strategy during the first phase of the pandemic, with only symptomatic patients being tested by PCR and limited use of serological tests, could have led to an underestimation of the real infection rate. However, seroprevalence data from Belgium seem to confirm the low infection rate in the CF population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Belgium evaluated 149 patients with CF between April and May 2020 and measured their anti-SARS-CoV-2 IgM and IgG levels. A lower seroprevalence was noted in individuals with CF (2.7%) versus the general population (4.9%), suggesting a lower infection rate [14] . An overview study conducted in Italy concluded that the infection rate was indeed lower in the CF population than that of the general population [15] , [16] .…”
Section: Epidemiology Of Sars-cov-2 In Cystic Fibrosismentioning
confidence: 82%
“…However, data suggest that the SARS-CoV-2 infection rate is lower in those with CF compared to the general population [11] , [12] , [13] , [14] , [15] , [16] . This is likely the result of rigorous infection control measures practiced by the CF community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it was clear that COVID-19 could be a serious condition for some people with CF, infection with SARS-CoV-2 for most people with CF is less severe than originally feared. We have also learned that there can be asymptomatic infection, with evidence coming from serologic assessment of a CF cohort [4] , although the prevalence was low, perhaps lower than the general population. One hypothesis for this observation is that CF patients and families are more attuned to the need for infection control measures and are therefore better at shielding themselves to minimize the risks of infection.…”
mentioning
confidence: 99%